Dictatorial Shouts, Whispers and Silences. Chilean Historiography and Pinochet S Dictatorship [Gritos, Susurros y Silencios Dictatoriales. la Historiografía Chilena y la Dictadura Pinochetista] - Valdivia-Ortiz de Zarate, V (State University of Santa Catarina, 2018)
This article reviews the historiography concerning the Chilean dictatorship led by General Augusto Pinochet. It claims that the dictatorial period has not established, at least in Chile, a consistent and sustained field of studies, as attention has tended to focus more on its repercussions in the postdictatorial period and the complicities of civilian governments on such continuities, as well as on the different "roads" to socialism and the experience of the Popular Unity. These emphases are connected to Chile s current political debates about the feasibility or desirability of dismantling Pinochet s legacies, with their attendant incidence on an unbalanced historiographic production: some topics have been analized in excess, others have received less attention, and many more have been simply ignored. Shouts, whispers and silences are the metaphors here employed to convey those tendencies. © 2018 RCN Publishing Company Ltd. All rights reserved.